MUCOSECTOMY IN COMPLICATED APPENDICITIS - Syeda Rifaat Qamar Naqvi (Army Medical College Rawalpindi, 2021)
Objective: To describe the technique and results of mucosectomy; A surgical technique that is easy to perform, and has a lower morbidity and complication rate as compared to standard appendectomy in cases of complicated appendicitis.